PERBAIKAN STATUS Hb (HEMOGLOBIN) PADA IBU HAMIL TRIMESTER PERTAMA DENGAN JUS DAUN BAYAM (Amaranthus tricolor. L) - Titik Wijayanti (Biology Education Department, Universitas Insan Budi Utomo, Malang, Indonesia, 2016)
Anemia is a patologies condition which the hemoglobin concentration under the normal. Anemia ferrum (Fe) deficience usually attacts to womens pragnance, that is corelated with highly abortion, mother and baby born mortality, baby borned with low weight and IQ level defences. Spinach (Amaranthus tricolor. L) are rich vegetable ferrum that is 3,9 mg/100 g. Aim the research are known the effects of spinach leaf juice to increasing hemoglobin on womens pragnance (first trimester). Result of normality, homogenity and paired-t test shown that spinach leaf juice effected increasing hemoglobin on womens pragnance at first trimester. Ability of ferrum (Fe) on spinach to increasing hemoglobin that is caused by some factors. One of it’s estimated caused by a component that effect the ferrum absorbtion in the women pragnance blood’s namely ascorbic acid. It’s compound estimated to accelerate the ferrum absorbtion in the woman pragnance blood’s.